Convergence of energy efficiency policy in Ukraine and developed countries: the causal relationship between key determinants - Lyulyov, Oleksii (<center>Conference Proceedings Determinants Of Regional Development</center>; No 2 (2021): Conference Proceedings - VIII International Scientific Conference Determinants of Regional DevelopmentDO - 10.14595/CP/02/008, 2021)
The unbalanced and unsynchronised ecological, energy, and economic policies of Ukraine provoke the dilemma on the priority of the new trajectory of the country’s development and achievement of Sustainable Development Goals in energy-saving and increasing energy efficiency. Thus, the exacerbation of environmental conflicts, a huge energy consumption level, and increasing greenhouse gas emissions requires developing effective mechanisms to overcome and eliminate the mentioned issues. It should be realised with the simultaneous increase in the country’s energy security. The paper aimed to check the convergence of the energy efficiency policy in Ukraine and developed countries. For the assessment of the energy policy efficiency, the study used the core indicators of The Energy Trilemma Index, which grouped by the three vectors: energy security; energy equity, environmental sustainability. The investigation object was Ukraine and ЕU developed countries (Lithuania, Latvia, Poland, Croatia). These countries have two mutual characteristics: in the years 1990-1992 the aforementioned countries started political transformations from refusing the monopoly of the Communist Party; in economic terms – the transition from centralised governance to the market economy. The time for analysis – the years 2000-2020; the dataset was obtained from the following databases: World Bank, Eurostat and Ukrstat. The study applied the σ-convergence and β-convergence for the analysis. The empirical results confirmed that reorientation of the Ukrainian energy sector based on implementing the instruments for declining the energy gaps could be the core drivers to synchronise the national energy policy with strategic targets under Sustainable Development Goals. Besides, it requires using cost-effective, innovative energy technologies and developing new options for the country's sustainable energy development. The study's findings could be applicable in resolving the contradictions in implementing the Ukrainian energy policy.